Taphonomy and palaeoecology of a monospecific microvertebrate bonebed: behavioural implications for the late Permian (Lopingian) parareptiles - Mukwevho, Lutendo (University of the Witwatersrand, Johannesburg, 2024)
Sociality in the vertebrate fossil record is a dynamic and fast-expanding area of research. Natural history observations of living animals are crucial for understanding and categorizing sociality, but these observations are not feasible for extinct species. Monotaxic bonebeds provide unique opportunities to conceptualize the social behaviours of these extinct animals. An unusual bonebed (SAM-PK-K11289) discovered in the uppermost Permian strata of the Balfour Formation, Karoo Supergroup, in the Eastern Cape presents a window into the sociality of Late Permian reptiles. The use of propagation phase-contrast synchrotron X-ray microcomputed tomography permitted the 3D reconstruction of skeletal elements in SAMPK-K11289, allowing the taxonomic identification of the individuals in the bonebed as most likely belonging to Owenetta. This is the largest aggregation of Owenetta individuals known to date, with a minimum number of 31, which are all very similar in body size. The ontogenetic profile of SAM-PK-K11289 was interpreted by analysing the size distribution of duplicate elements and by making comparisons with other Owenetta and procolophonid specimens. The specimens in the bonebed are all osteologically immature, indicating that they are juveniles. The bonebed occurs in a pedogenically modified ripple cross-laminated siltstone suggesting that a low-energy fluvial sedimentation likely contributed to the modification, disturbance and disarticulation of elements before the bonebed was buried at or very close to the death site. This bonebed provides novel information that directly challenges the popular belief that reptiles and their ancestors are non-social or asocial. Considering the overall circumstances of the bonebed, I hypothesize that Owenetta rubidgei juveniles were socially gregarious and this behaviour may have been induced or influenced by environmental changes during the early extinction phase of the end Permian mass extinction in the Karoo Basin.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Palaeontology, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Taphonomy; Bonebeds; Palaeoecology; Microvertebrate; Parareptiles; Behaviour; Late Permian; UCTD; SDG-15: Life on land; SDG-4: Quality education